ANALISIS FAKTOR-FAKTOR KEUANGAN TERHADAP KINERJA PERUSAHAAN DENGAN FIRM SIZE SEBAGAI KONTROL - Hasanah, Alfi; Wahyuni , Ajeng (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2025)
This research aims to analyze the effect of Debt to Equity Ratio (DER), Working Capital, and Cost of Goods Sold (COGS) on the financial performance (ROA) of manufacturing companies listed on the Indonesia Stock Exchange (ISE) from 2020 to 2023, with company size as a control variable. The problem being studied is how DER, Working Capital, COGS, and company size partially and simultaneously influence financial performance. The method used is a quantitative approach, and the sampling was conducted using purposive sampling, resulting in 14 companies and 56 observations. The results show that DER, Working Capital, COGS, and company size have a significant effect on financial performance both partially and simultaneously. This is useful as a reference for management and investors to understand aspects that can support company performance